Effect of Different Organic Acids on Survival of Larvae and Control of Water Microflora in Milk fish (Chanos chanos) Hatchery System - Kumar, N. Ranjit; Kumar, P. Prasanna; Siddaiah, G. M.; Murugadas, V.; Basha, K. A.; Sivaraman, G. K.; Prasad, M. M. (Fishery Technology, 2018)
This study reports the use of organic acids (acetic, malic, formic and citric) in fish larval rearing systems for survival and controlling the microflora of rearing water. The milk fish (Chanos chanos) larvae was treated for 10, 15, 30 and 60 min with seven concentrations (%) viz., 1, 0.2, 0.1, 0.075, 0.05, 0.025 and 0.02 of organic acids respectively. The percentage survival was zero (1, 0.2, and 0.1% conc) for all the organic acid at various time periods. The effective concentrations for treating fish larvae are 0.05, 0.05, 0.025 and 0.075% concentrations of acetic, malic, formic and citric acid, respectively where 100% survival was observed. Similarly, when the larval rearing water was treated with different concentrations of same organic acids and time period, complete inhibition of microbial flora was observed (1, 0.2 and 0.1% conc) for all organic acids at various time periods. However, at concentrations less than 0.1%, total bacterial count (TBC) and presumptive Vibrio count (PVC) were found in the range of 3.19 to 5.75 and 2.22 to 3.58 log 10 cfu ml-1. In contrast, TBC and PVC in control group were found in the range of 6.37 to 6.90 and 4.35 to 4.74 log 10 cfu ml-1. The acid treatment with concentrations of 0.075, 0.05 and 0.025 except formic acid at 0.025, 0.020 significantly (p<0.05) improved the survival rates of fish larvae and reduced both TBC and PVC in larval rearing water. The present findings strongly recommend the use of organic acids for treating fish larvae for improved survival and also for reducing pathogenic bacterial load from larval rearing waters.